Asas Dekonsentrasi dan Asas Tugas Pembantuan dalam Penyelenggaraan Pemerintahan - Andi Pitono (Universitas Riau, 2011)
A principle is base, guidance or something that considered as truth; that become thinking purposeand principles of guidance. Principles of Government come to be general principles as base and rule inconducting appropriate government, therefore the governmental conduct can be polite, fair and honor, freefrom cruelty, rule violation, abuse action of authority and too authoritative action. According to ConstitutionNo 32 in 2004, it states that in conducting governmental affairs, Government rules by itself or gives away apart of the affairs to its elements or subsidiary in district or gives it to regional government and/or villagegovernment. In line with conducting governmental affairs as regional authority, the regional carries outautonomy widely in order to rule and accomplish governmental problems on its own based on autonomy and“tugas pembantuan”.